Synthesis and In-vitro Photodynamic Studies of the Superparamagnetic Chitosan Hydrogel/Chlorin E6 Nanocarriers - Reza Saboktakin, Mohammad; M. Tabatabaie, Roya; Satarzade Amini, Fahimeh; Maharramov, Abel; Ali Ramazanov, Mohammad (Medicinal Chemistry, 2013)
The objective of the present study was to develop superparamagnetic chitosan(CS) - dextran sulfate(DS) hydrogels as a intelligent drug system for effective carrying of Chlorin E6(chn E6) photosensitizer to cancer cells. This system can be detectable by magnetic Resonance Imaging technique. The study shows that the lifetime of the triplet state for chn E6 photosensitizer is significantly increase when encapsulate into hydrogel. In addition to the possible enhancement of 1O2 generation, other advantages to incorporating chn E6 -based PS agents into hydrogel include the ability to solubilize these generally hydrophobic agents, the small and uniform size of hydrogels, and potential for passive targeting of solid tumors via the enhanced permeation and retention effect decreasing systemic photosensitization.
Keywords: intelligent carrier